2015
DOI: 10.1016/j.jcrs.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Combined intrastromal astigmatic keratotomy and laser in situ keratomileusis flap followed by photoablation to correct post–penetrating keratoplasty ametropia and high astigmatism: One-year follow-up

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…16,17,21–30 Therefore, studies regarding the association of several different techniques have been published with promising results. 23,36,37…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17,21–30 Therefore, studies regarding the association of several different techniques have been published with promising results. 23,36,37…”
mentioning
confidence: 99%
“…16,17,[21][22][23][24][25][26][27][28][29][30] Therefore, studies regarding the association of several different techniques have been published with promising results. 23,36,37 This article aims to assess the outcomes of the association of ICRS and PRK for the treatment of high PKA.…”
mentioning
confidence: 99%
“…Included studies were published between 1992 and 2022; 23 were prospective clinical trials and 8 were retrospective. 4,15,16,24–52 Almost all studies had 1 treatment arm, except the study by Huang et al, which had 2 arms. 36 Six studies were conducted in the United States; 5 in Brazil; 4 in Canada; 3 in Italy; 3 in Turkey; 3 in Germany; and 1 each in Australia, Egypt, Iran, Japan, Korea, England, and Spain.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies reported patients' sex; the percentage of female patients was 43.6% of the total number of participants. 4,15,16,24,[26][27][28][29][30][31][32][33][35][36][37][39][40][41][43][44][45][46][47]49,50,52 Follow-ups ranged from 1 month to 56 months. Seventeen studies performed LASIK; 12 studies performed PRK, of which 2 performed additional refractive procedures (PTK, intrastromal corneal ring segments) and 1 performed laser-assisted subepithelial keratectomy (LASEK) on a comparison group.…”
Section: Literature Findingsmentioning
confidence: 99%
See 1 more Smart Citation